Nas encruzilhadas de Carolina Maria de Jesus: cartografia da poeticidade na obra antologia pessoal - Ferreira, Carolina dos Santos (2023)
This research aims to investigate the aesthetic and poetic project of Carolina Maria de Jesus in her book Antologia Pessoal (1996), starting from the maneuvers' cartography of the poetic discourse and the analysis of the poems present in the work, anchored in the study of poetic theories. It seeks to understand how the poetic language of Carolina de Jesus leverages the process of uprooting the being, and, from its poetics, breaks with the dominant hegemonic thought and amalgamates with black poetics. A concept woven here from the thought of bell hooks, with contemporary poetry as a movement of dissociation and anachronism with its time while allowing other forms of being, outside the subjectivity forged in the hegemonic system. I propose, in order to reflect on the traditional concept of poetics by putting the theoretical propositions of bell hooks (1997, 1999, 2012), Dénètem Touam Bona (2020), Édouard Glissant (2011) and Leda Maria Martins (2021) into dialogue and friction. For the execution of the project, the foundations of a qualitative, exploratory and descriptive research will be used, also using the analytical, hypotheticdeductive method